Improving Bodily Kinesthetic Competence Through Simple Bowling Game to Kindergarten Chlidren of Jungle School Semarang in the Academic Year 2023/2024 - Ratno; Santoso, Didik Ardi; M.Sukiram; Pramita, Dian (Jurnal Pendidikan Anak Usia Dini, 2024)
This research was conducted to explain the application of simple bowling game to improve bodily kinesthetic competence to the kindergarten children of Jungle School Semarang in academic year of 2023/2024 and to find out the result of conducting simple bowling game to improve children’ bodily kinesthetic competence. This classroom action research applied 2 cycles. In each cycle consisted of planning, acting, observing, and reflecting. Subject of this research was the children of Jungle School kindergarten Semarang which consisted of 15 children. The researcher got data collection through observation and documentation. The result of this research found in before cycle that only three children or 20% who passed standard criteria of BSH (expected progress).  On the other hand, there were 12 children or 80% in criteria of MB (starting on progress). In the first cycle, there was improvement in each meeting. Children with the criteria of BSH was 7 children (46,7%). Based on the result so can be inferred that in the cycle I has not passed the passing grade of research indicator, so the researcher moved on to the cycle II. The result on cycle II showed that one child (6.6%) passed the indicator standard of BSB (well progress). In addition, there were about 12 children (80%) passed the criteria of BSH (expected progress). Then only 2 children (13,4%) who did not pass the criteria or they were in the criteria of MB (starting on progress). Based on the result on the cycle II, it showed that 80 % of children have passed the passing grade criteria, so the research did not continue to the next cycle.